Risk Management Analysis in Minimizing the Risk of Problematic Credit on KECE Loans at BRI Medan Regional Office - Damanik, Anisa Nandita Hafiz; Simanjorang, Feronica (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to find out and analyze the factors causing the risk of problem credit and to know and analyze risk management in minimizing the risk of problem credit on KECE loans at the BRI Medan regional office. The form of research used in this research is descriptive qualitative research. Data was obtained from primary and secondary data. The results of the research show that problematic credit on KECE loans at BRI Medan regional office is caused by internal and external factors, the implementation of risk management carried out by BRI Medan regional office on KECE loans, namely active supervision of the board of commissioners and directors (managers), adequacy of policies, procedures and determination risk limits, processes for identifying, measuring, monitoring and controlling risks and internal risk control systems.